Epidemiology and Outcomes of Infectious Spondylodiscitis in Hemodialysis Patients. Issue 12 (15th June 2018) - Lu, Yueh-An; Sun, Wei-Chiao; Kuo, George; Chen, Chao-Yu; Kao, Huang-Kai; Lin, YuJr; Lee, Chia-Hui; Hung, Cheng-Chieh; Tian, Ya-Chung; Ko, Yu-Shien; Hsu, Hsiang-Hao
Abstract : Study Design: A retrospective study of patients who were hospitalized for infectious spondylodiscitis over a 13-year period. Objective: To elucidate the epidemiology and prognostic factors of infectious spondylodiscitis in hemodialysis (HD) patients and to identify the impact of HD on infectious spondylodiscitis. Summary of Background Data: Only a few case studies of infectious spondylodiscitis in HD patients can be found in the literature. Reports of prognostic factors are limited and patients' outcomes have not been well described. Methods: The cases of 1402 patients who were hospitalized for infectious spondylodiscitis over a 13-year period were retrospectively reviewed. Of these, 102 patients on maintenance HD were enrolled in this study. Cox proportional hazard model was used to evaluate the risk factors of mortality and recurrence. Results: The 102 enrolled patients had an average age 63.3 ± 11.2 years old and male-to-female ratio of 1:1.04. Back pain was present in 75.5% of patients and the most commonly infected site was the lumbosacral spine. Infection associated with vascular access was identified in 31.4% of patients. The prevalence of dialysis via central venous catheters was higher than prevalent HD patients. Methicillin-resistant Staphylococcus aureus was the most common pathogen, followed coagulase-negative staphylococci. The patients' in-hospital survival rate was 82.4%; their vascular access survival rate was 75.5%; their 1-year survival rate was 78.4%, and their 1-year recurrence rate was 20.2%. Congestive heart failure was associated with an increased 1-year mortality. Other variables exhibited no significant relationship with patients' in-hospital mortality, 1-year mortality or recurrence. Conclusion: The characteristics and outcomes of infectious spondylodiscitis in HD patients were elucidated. Most of the demographic and clinical variables, evaluated upon admission, did not predict mortality or recurrence. Level of Evidence: 3